The witness - Henderson, Dee (Tyndale House, 2006)
After witnessing a murder eight years ago, Amy Griffin chose to accept a life in the shadows in order to protect her sisters' lives, but now that the man who wants Amy dead sees the sisters as the only way to locate her. Facing the future will take a faith deeper than any of them currently knows.